Analyzing the Impact of TikTok-Video Content Marketing Strategy and Entrepreneur Personal Branding on Consumer Purchase Intention in the Used Car Market: A Case Study of Mestika Jaya Mobil Showroom: Menganalisis Dampak Strategi Pemasaran Konten Video TikTok dan Personal Branding Pelaku Usaha terhadap Minat Beli Konsumen di Pasar Mobil Bekas: Studi Kasus Showroom Mestika Jaya Mobil - Wilson Wiranata; Petrus Loo; Jupert Jasser Abellana; Abdullah Sirad (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
The development of digital marketing has encouraged used car businesses to leverage social media, particularly TikTok. This study aims to analyze the influence of content marketing and personal branding on purchase intention for used cars at Mestika Jaya Mobil Showroom, Medan. The research design employed a descriptive quantitative approach with a sample of 100 respondents obtained through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression using SPSS, accompanied by validity and reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination. The findings reveal that content marketing and personal branding significantly affect purchase intention, both individually and simultaneously. The model explains 74.2% of the variance in purchase intention. These results highlight the effectiveness of content marketing strategy through TikTok and entrepreneurs’ personal branding in enhancing purchase intention in the used car market. This study offers practical insights for used car businesses to optimize their marketing strategies.